DESIGNING BUSINESS PERFORMANCE MEASUREMENT INSTRUMENTS WITH SHORTTAN BALANCED SCORECARD AT CAFE RED &BLUE TANJUNGPINANG - Satriadi Satriadi; Liza Liza; Maulana Mega Putri Dwi Sukmawati; Lady Fitri Ayu Sihombing; Mario Radithya Tama (Proceeding of The International Conference on Economics and Business, 2022)
Performance management in question is with the aim of increasing the strategic focus and effectiveness of the company in ensuring continuous improvement of individual and team performance. The most popular approach is to use the BSC (Balanced Scorecard). Cafe Red&Blue wants to grow and maintain its business. Therefore, in this study we want to design an instrument for measuring performance at Red&Blue cafes using the BSC. The initial stage in designing the instrument is to conduct internal and external analysis to determine the position of the business in the industry and the strategy that must be used. The SWOT approach is used in the analysis of the internal and external environment. From the SWOT analysis, it can be seen that the Red&Blue cafe is in quadrant I position. The strategy that must be applied is an offensive and defensive strategy as a complement. This strategy requires Red&Blue to improve its marketing strategy in order to bring even greater opportunities to the business. The next stage is through the formulation of strategic objectives, the objectives of which are designed; increase profits, increase customer loyalty, improve relationships with new customers, develop quality products with innovation, develop good and quality services, improve employee job satisfaction, increase employee skills, and knowledge employee knowledge. The eight strategic objectives are translated into 2 key financial performance indicator (KPI) perspectives, 3 internal business process KPIs, 4 customer KPI perspectives, and 5 KPI growth and learning perspectives, with targets for each KPI set based on discussions with Red&Blue cafe owners.